1979
DOI: 10.1080/00207177908922706
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate root loci: a unified approach to finite and infinite zeros

Abstract: A MacLaurin's series expansion is used to approximate the individual sheets of the characteristic gain function of a linear multivariable system in terms of its state space matrices, at the point at infinity on the frequfency plane for smlall values of characteristic gain. This yields the asymptotic root locus directions for systems with one or more sets of closed loop poles going to infinihy for large feedback gains. A bilinear transformation on the frequency variable is used to allow the approximation at any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Much of the literature on multivariable root locus assumes that the system satisfies the SNS assumption [10,14,15]. We show in this section that the proposed controller (4.35) ensures that the augmented plant satisfies SNS.…”
Section: Simple Null Structurementioning
confidence: 97%
See 2 more Smart Citations
“…Much of the literature on multivariable root locus assumes that the system satisfies the SNS assumption [10,14,15]. We show in this section that the proposed controller (4.35) ensures that the augmented plant satisfies SNS.…”
Section: Simple Null Structurementioning
confidence: 97%
“…We follow the developments of [14] closely and explore the asymptotic behaviour of the multivariable root locus first. It will be shown that the unbounded closed-loop poles approach infinity in several Butterworth patterns whose orders, under certain assumptions, are equal to the orders of infinite zeros of the system.…”
Section: Multivariable Generalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been extensively studied in the control literature. Typical references include Shaked (1976Shaked ( ,1978, Kouvaritakis (1978), Kouvaritakis and J. M. Edmunds (1979) , and more recently Sastry and Desoer (1983). A geometric approach was developed by Willems (1981Willems ( ,1982.…”
Section: Singular Cheap and High Gain Controlmentioning
confidence: 99%
“…The asymptotic behavior has been extensively studied by Kouvaritakis and Shaked [3], Kouvaritakis [4], Kouvaritakis and Edmunds [5], Owens [11,12], MacFarlane and co-workers [2,19], Kokotovic, et. al [22], and by Brockett and Byrnes [10].…”
Section: Section 1 Introductionmentioning
confidence: 99%